The Mediating Role of Health Literacy in the Effect of Health Service Quality on Patient Loyalty - YAŞAR, Mehmet Emin; BAYDAŞ, Abdulvahap; YALMAN, Fuat (International Journal of Contemporary Economics and Administrative Sciences, 2020)
The purpose of this study is to determine the mediating role of health literacy in the impact of health service quality on patient loyalty. The universe of the research is the patients who have outpatient treatments from Gaziantep University Şahinbey Research and Application Hospital. In this study, quantitative research method was used and the data were collected from 420 patients through face to face questionnaire technique. In the study, descriptive statistics, confirmatory factor analysis and path analysis techniques were used. SPSS and AMOS software were used for data analysis. According to the results of the research, it was found that the dimension representing the health service quality of the hospital at the best level was ati Empathy, and the dimension representing the health literacy level of the patients at the best level was Judging the Accuracy of Health News”. Within the framework of direct relations of variables in the research model, it was found that health service quality has a statistically significant and positive effect on patient loyalty; that health service quality has a statistically significant and positive effect on health literacy; that health literacy has a statistically significant and positive effect on patient loyalty, and that health literacy has a mediating role in the relationship between health service quality and patient loyalty, which is statistically significant and positive.